(3GdadGM aj GdfUjMI hGdGJVGMs - (3GdbTJGdj , eMeO Hf TYjH Hf eMeO GdMLGRj GdTYjHj GdGHTjgj,J (B1035 (3g` s ((3eMeO CHhaGTg GdefRdi s)
(3ChdgG (B:s
(3aCbhd hHGddg GdJhajb GdhbJ YHGQI Yf GdJLdj ddYHO ef GdMb JHGQc hJYGdi aj GdJLdj hgh GddHS dbhdg JYGdi(B:" (3Hd ge aj dHS ef Ndb LOjO s
(3BNQgG (B:s
(3hgPG cdg aj ebGe GdJaUjd hCeG ebGe CMOjI GdYjf adG jQi eY GdMb GKfjf hGdMeO ddg QH GdYGdejf s
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B200s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3JUha(B) s
Keywords: (3GdJUha hGdBOGH GdTQYjIs